Peripheral blood cells chimerism after unrelated cord blood transplantation in children: kinetics, predictive factors and impact on post‐transplant outcome. (29th April 2014) - Elkaim, Elodie; Picard, Christophe; Galambrun, Claire; Barlogis, Vincent; Loundou, Anderson; Curtillet, Catherine; Oudin, Claire; Thuret, Isabelle; Chambost, Hervé; Michel, Gérard
Summary This study aimed to describe kinetics of complete donor chimerism occurrence (cDC, >99·9% donor) after unrelated cord blood transplantation (UCBT), to identify its predictive factors and its impact on post‐transplant outcome. Ninety‐four children who received single UCBT after a myeloablative conditioning regimen had blood chimerism evaluation at predefined post‐transplant dates, using a real‐time polymerase chain reaction method with 0·1% sensitivity. Cumulative incidence of cDC at 1 year post‐transplantation was 61·8%. Three predictive factors were identified in multivariate analysis: history of malignant disease (P = 0·03), older age (above 2·16 years, the first quartile of age, P = 0·0055) and higher level of cord/recipient human leucocyte antigen mismatch (4/6 vs. 5‐6/6, P < 0·001) increased the probability of post‐transplant cDC. Although graft cell dose had a strong impact on haematological recovery, it did not apparently influence cDC occurrence. Early cDC (i.e. more than 99·9% donor chimerism on days 15–30 post‐transplant) appeared useful to predict engraftment (P = 0·003) as well as acute and chronic graft‐versus‐host disease (GvHD). Severe acute or chronic GvHD never occurred in patients with DC ≤99·9%, suggesting than even minimal residual host haematopoiesis is associated with a very low risk of GvHD after UCBT.